REPRESENTATION OF INDONESIA IN WIKIPEDIA - Sunarsih (International Journal of Linguistics and Discourse Analytics, 2020)
The objective of this study is to describe the representation of Indonesia in Wikipedia article. The approach applied in this study is corpus-based discourse analysis. This approach concerned with the key word â€œIndonesiaâ€ and how it conveyed meaning related to the other words around (collocation) in the left and right side of the word â€œIndonesiaâ€. By analyzing the collocation, the representation of Indonesia is interpreted and input as the meaning property of the word â€œIndonesiaâ€. The finding of this study shows that the word â€œIndonesiaâ€ in Wikipedia article contained meaning components such as Indonesia is a country whose rich cultural and natural resources, long history; developing technology; developing economy; facing some problem; actively participating in international affair and sport competition.